Vehicle good-appearance anti-aging recycled polypropylene composite material and preparation method thereof

By preparing a good-looking anti-aging cycle regenerated polypropylene composite material for automotive use containing specific components, and using an extruder and vibrating screen to remove impurities, the aging problem caused by doping impurities during the recycling process of existing regenerated polypropylene materials is solved, and the material has good aging resistance and good appearance are achieved.

CN119661931APending Publication Date: 2025-03-21CHONGQING ORINKO TECH CO LTD CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411800030.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing recycled polypropylene materials are easily doped with other resins, fillers, metals and impurities during large-scale recycling, resulting in pitting and bulging on the appearance surface, and are prone to aging in light and thermal environments, reducing material performance.

Method used

It is made of a good-looking anti-aging cycle regenerated polypropylene composite material for automotive use, which is prepared from components such as regenerated polypropylene mixture, polypropylene, toughening agent, filler, weathering agent, antioxidant, long-acting antioxidant, modified epoxy resin, metal passivator and metal carbonate hydrate. It removes impurities through equipment such as extruders and vibrating screens to improve appearance and aging performance.

Benefits of technology

It achieves good heat-resistant and photo-resistant performance of composite materials, and has no adverse phenomena such as pitting and bulging, and meets the requirements of automobile use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to an automotive anti-aging recycled polypropylene composite material with good appearance and a preparation method thereof, and the automotive anti-aging recycled polypropylene composite material with good appearance is prepared from the following components in percentage by weight: 10%-90% of a recycled polypropylene mixture, 5%-70% of polypropylene, 1%-25% of a toughening agent, 1%-22% of a filler, 0.2%-0.5% of a weather-proof agent, 0.1%-0.8% of an antioxidant and 0.1%-0.2% of a long-acting antioxidant, 0.1%-1.5% of modified epoxy resin, 0.1%-1.0% of metal deactivator and 0.1%-0.25% of metal carbonate hydrate. The automotive anti-aging recycled polypropylene composite material with good appearance has good heat aging resistance and light aging resistance, has no bad phenomena such as pocking marks, bumps and the like, and meets the use requirements of automobiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycled polypropylene composite materials, and in particular to a good-appearance anti-aging recycled polypropylene composite material for vehicles and a preparation method thereof. Background Art

[0002] Polypropylene is a crystalline polymer material formed by the polymerization of propylene. It appears as white particles and is odorless and non-toxic. It is widely used in the automotive, home appliances, electronics, packaging, building materials and furniture fields due to its low density, low price, easy molding, low production cost and easy adjustment of material properties through modification.

[0003] With the development of economy, the global polypropylene production is gradually increasing, and a large amount of waste polypropylene plastics are produced, which brings great pressure to the environment. The efficient reuse of polypropylene plastics can effectively alleviate the environmental pressure and reduce the manufacturing cost of plastic products. In the automotive field, the EU is pushing the automotive industry towards a more sustainable circular economy model, requiring automakers to use at least 25% recycled plastics in new models. Therefore, the ecological design of automobiles and the use of recycled raw materials have attracted more and more attention from OEMs, and the use of recycled materials to replace some new materials in related automotive parts has become a new trend with broad development and application prospects.

[0004] At present, the recycled polypropylene materials on the market, whether they are post-consumer recycled or post-industrial recycled, may be doped with some other resins, fillers, metals and impurities during the large-scale recycling process. The doped high-melting point resins, metals and impurities cannot be integrated with polypropylene during the recycling process, resulting in pitting and bulging on the surface; the doped other resins are easily degraded under light and heat during the recycling process, which not only reduces the mechanical properties of the material but also aggravates the light aging and thermal aging of the material; the metal ions released by the doped metals will catalyze the free radical chain reaction in the degradation process of polypropylene and accelerate the light aging and thermal aging of the material; the doped impurities and the acidic substances and anions carried by the catalyst residues in the polymerization process of the polypropylene raw materials will reduce the activity of the additives and affect the thermal aging and light aging properties of the composite materials. Summary of the invention

[0005] Based on this, the purpose of the present invention is to provide a good appearance anti-aging recycled polypropylene composite material for automobiles and a preparation method thereof, so as to solve the problems existing in the existing recycled polypropylene materials.

[0006] To achieve the above object, the present invention adopts the following technical solutions: The invention first provides a good-appearance anti-aging recycled polypropylene composite material for vehicles, which is prepared from the following components in percentage by weight: 10%-90% of recycled polypropylene mixture, 5%-70% of polypropylene, 1%-25% of toughening agent, 1%-22% of filler, 0.2%-0.5% of weathering agent, 0.1%-0.8% of antioxidant, 0.1%-0.2% of long-acting antioxidant, 0.1%-1.5% of modified epoxy resin, 0.1%-1.0% of metal passivator and 0.1%-0.25% of metal carbonate hydrate.

[0007] As a further improvement of the above scheme of the present invention, it is prepared from the following components in weight percentage: 30% to 50% of recycled polypropylene mixture, 20% to 40% of polypropylene, 8% to 15% of toughening agent, 10% to 22% of filler, 0.2% to 0.4% of weathering agent, 0.3% to 0.6% of antioxidant, 0.1% to 0.19% of long-term antioxidant, 0.5% to 1.0% of modified epoxy resin, 0.4% to 0.8% of metal passivator, and 0.1% to 0.2% of metal carbonate hydrate.

[0008] As a further improvement of the above scheme of the present invention, the recycled polypropylene mixture is composed of one or more of a resin, a filler, a metal and impurities, the resin is at least one of PP, PE, ABS, PC, PBT, PET, PA6, and PA66, and the filler is at least one of talcum powder, calcium carbonate, mica, wollastonite, magnesium sulfate whisker, and barium sulfate; the ash content of the recycled polypropylene mixture is ≤5%, and the density is ≤0.93g / cm 3 , polypropylene content ≥90%.

[0009] As a further improvement of the above solution of the present invention, the recycled polypropylene mixture is post-consumer recycled polypropylene material and / or post-industrial recycled polypropylene material.

[0010] As a further improvement of the above solution of the present invention, the polypropylene is homopolymer polypropylene and / or copolymer polypropylene; And / or, the toughening agent is at least one of ethylene-octene copolymer, polyethylene, hydrogenated styrene-butadiene-styrene block copolymer and ethylene propylene diene monomer rubber; And / or, the filler is at least one of talc, calcium carbonate, mica, wollastonite, magnesium sulfate whisker, and barium sulfate; And / or, the weathering agent is hindered amine light stabilizer LA-402AF or hindered amine light stabilizer UV-3808PP5.

[0011] As a further improvement of the above scheme of the present invention, the antioxidant includes a primary antioxidant and a secondary antioxidant, the primary antioxidant is a composite of a hindered phenol antioxidant 1076 and a hindered phenol antioxidant 1098 in a mass ratio of 1:(0.2-0.3), and the secondary antioxidant is a phosphite antioxidant 168; And / or, the long-acting antioxidant is at least one of didodecanol thiodipropionate DLTDP and distearyl thiodipropionate DSTP.

[0012] As a further improvement of the above scheme of the present invention, the modified epoxy resin is prepared from an epoxy resin modified by an alicyclic epoxy polysiloxane, wherein the number average molecular weight of the alicyclic epoxy polysiloxane is 800-1200 g / mol and the epoxy value is 0.5-0.8.

[0013] As a further improvement of the above scheme of the present invention, the metal passivator is at least one of the hydrazide compounds N,N'-bis[β(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, (3,5-di-tert-butyl-4-hydroxyphenyl)propionate oxalyl(diimino-2,1-ethylene ester), and N-salicylicylaminophthalimide; And / or, the metal carbonate hydrate has a MgO content of 34.1% to 35.8%, an Al 2 O 3 The content is 18.5%~21.5%, MgO, Al 2 O 3 The molar ratio is 0.042~0.05:1.

[0014] The present invention also provides a method for preparing the above-mentioned automotive good appearance anti-aging recycled polypropylene composite material, which comprises the following steps: S1. Weigh the recycled polypropylene mixture, polypropylene, toughening agent, filler, weathering agent, antioxidant, long-acting antioxidant, modified epoxy resin, metal passivator and metal carbonate hydrate in proportion, and mix the filler, recycled polypropylene mixture, polypropylene, toughening agent, weathering agent, antioxidant, long-acting antioxidant, epoxy resin, metal passivator and metal carbonate hydrate accounting for 50 to 100% of the total weight of the filler to obtain a premix; S2. Place a magnet rack above the main feed port of the extruder (i.e., the location where all premixes need to pass); S3. A filter mechanism is provided at the connection between the barrel and the die of the extruder; S4. Place a magnet rack at the discharge port of the vibrating screen; S5. The premix is ​​added from the main feed port of the extruder, and the remaining filler is added from the side feed port of the extruder, melted, extruded, granulated, and screened with a vibrating screen to obtain a good appearance anti-aging recycled polypropylene composite material for automobiles.

[0015] As a further improvement of the above scheme of the present invention, in step S1, the mixing is carried out in a high-speed mixer at a speed of 450 to 600 rpm for 50 to 80 seconds; And / or, in steps S2 and S4, the magnetic field strength of the magnet frame is 10000-15000 Gs, and the cleaning frequency of the magnet frame is 2-4 hours / time; And / or, in step S3, the filter mechanism includes three layers of filters, the mesh number of the middle layer filter is 80-120 meshes, the mesh number of the outer two layers of filters is 20-40 meshes, and the replacement frequency of the three layers of filters is 2-4h / time; And / or, in step S5, the rotation speed of the extruder is 450-600 rpm, the temperature of the first zone of the extruder is 100° C., the temperature of the remaining zones of the extruder is 170° C.-200° C., and the vacuum degree of the extruder is above -0.06 MPa; and the screening is to screen out particles with a particle size of 2-3.5 mm.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention inhibits the thermal oxidation aging of the resin in the recycled polypropylene mixture by introducing an antioxidant, introduces a long-acting antioxidant to produce a synergistic effect with the antioxidant, improves the thermal oxidation aging performance of the composite material, and controls the ratio of the antioxidant to the long-acting antioxidant to avoid excessive addition leading to stickiness during the light aging process; by introducing a modified epoxy resin, the epoxy group of the modified epoxy resin can react with oxygen to form a stable epoxy compound, thereby consuming the free radicals in the reactants and reducing the occurrence of oxidation reactions. At the same time, the active groups in the modified epoxy resin can also capture free radicals and convert them into stable compounds, thereby achieving the purpose of anti-oxidation; by introducing a weathering agent, the light aging of the composite material can be inhibited; the present invention achieves the purpose of improving the anti-aging performance of the composite material by introducing a weathering agent, an antioxidant, a long-acting antioxidant, and a modified epoxy resin.

[0017] 2. The present invention adds a metal passivator to form a complex with high thermal stability with the metal in the recycled polypropylene mixture, thereby inactivating the metal ions and inhibiting the thermal aging and light aging of the composite material; by introducing metal carbonate hydrates, the acidic substances and anions are embedded and bound to the inorganic matter of the hydrate, maintaining the neutral environment of the composite material, protecting the activity of each auxiliary agent, and improving the thermal aging and light aging stability of the composite material; the present invention achieves the purpose of improving the anti-aging stability of the composite material through the synergistic effect of the metal passivator and the metal carbonate hydrate.

[0018] 3. In the preparation process of the composite material, the present invention can remove magnetic metal impurities in the composite material by arranging a magnet frame on the extruder and the vibrating screen; adopt a relatively low twin-screw extruder temperature (100° C. in one zone and 170-200° C. in the other zones) to prevent the high-melting-point resin (PA6, PA66, PET, PBT, PC) in the twin-screw extruder barrel from melting in the composite material, and at the same time, the high temperature of 170° C.-200° C. can ablate the impurities; and then a filter mechanism is arranged at the connection between the extruder and the die to filter out the infusible high-melting-point resin, metal and ablated impurities; remove other resins, metals and impurities in the recycled polypropylene mixture to obtain a relatively pure composite material (even if it still contains a small amount of high-melting-point resin, metal and impurities, their diameter is less than 0.125 mm, which does not affect the appearance of the composite material), thereby achieving the purpose of improving the appearance.

[0019] 4. The automotive good-appearance anti-aging recycled polypropylene composite material of the present invention has good heat aging resistance and light aging resistance, has no undesirable phenomena such as pits and bulges, and meets the requirements for automotive use. DETAILED DESCRIPTION

[0020] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0022] The raw material information used in the following examples and comparative examples is as follows: The recycled polypropylene blend is GEM's PP B336-GY31; Polypropylene is K7227H from Guangzhou Petrochemical; The toughening agent is Dow POE 8842; The talc powder was KCM-6300 from Beihai; The weathering agent is ADK's LA-402AF; The primary antioxidants were BASF’s Irganox 1076 and Irganox 1098; The secondary antioxidant was Irgafos 168 from BASF; The long-acting antioxidant was PS800 from BASF; The metal passivator is MD1024 from BASF.

[0023] The above raw materials are only for illustrating the sources and components of the reagents used in the experiments of the present invention so as to fully disclose the information, and do not mean that the present invention cannot be realized by using other similar reagents or reagents provided by other suppliers.

[0024] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.

[0025] Example 1 This embodiment proposes a good appearance anti-aging recycled polypropylene composite material for automobiles, which is prepared from the following components in weight percentage: 10% recycled polypropylene mixture PP B336-GY31, 70% polypropylene K7227H, 8% toughening agent POE 8842, 10% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 0.5% metal passivator MD1024, and 0.2% metal carbonate hydrate. The MgO content in the metal carbonate hydrate is 34.1% to 35.8%, and the Al content is 0.1%. 2 O 3 The content is 18.5%~21.5%, MgO, Al 2 O 3 The molar ratio is 0.042~0.05:1.

[0026] The preparation method of the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment comprises the following steps: S1. Weigh the recycled polypropylene mixture, polypropylene, toughening agent, filler, weathering agent, antioxidant, long-acting antioxidant, modified epoxy resin, metal passivator and metal carbonate hydrate in proportion, and add 50 to 100% of the total weight of the filler, the recycled polypropylene mixture, polypropylene, toughening agent, weathering agent, antioxidant, long-acting antioxidant, epoxy resin, metal passivator and metal carbonate hydrate to a high mixer and mix at a speed of 450 to 600 rpm for 50 to 80 seconds to obtain a premix; S2. Place a magnet rack above the main feed port of the extruder (i.e. the position where all premixes need to pass). The magnetic field strength of the magnet rack is 10000~15000Gs, and the cleaning frequency of the magnet rack is 2~4h / time; S3. Add three layers of filter screen between the extruder barrel flange and the die flange. The mesh size of the two outer layers is 20-40 mesh, and the mesh size of the middle layer is 80-120 mesh. The replacement frequency of the three layers of filter screen is 2-4 hours / time; S4. Place a magnet rack at the discharge port of the vibrating screen. The magnetic field strength of the magnet rack is 10000~15000Gs. The cleaning frequency of the magnet rack is 2~4h / time; S5. Add the premix through the main feeding port of the twin-screw extruder, add the remaining filler in step S1 from the side feeding port, and plasticize and melt into a mixed melt through the extruder, wherein the speed of the twin-screw extruder is 450-600 rpm, the temperature zone 1 is 100°C, the other temperatures are 170°C-200°C, and the vacuum degree is above -0.06MPa; the mixed melt is extruded into material strips through a die, and after water cooling, it enters a pelletizer and is cut into plastic particles; the plastic particles are screened out with qualified particles of 2-3.5mm in diameter through a vibrating screen, and after falling into the discharge port of the vibrating screen, they are sucked into a homogenizing tank to obtain a good appearance anti-aging recycled polypropylene composite material for automobiles.

[0027] Example 2 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 21% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 0.5% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0028] Example 3 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 50% recycled polypropylene mixture PP B336-GY31, 11% polypropylene K7227H, 15% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 0.5% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0029] Example 4 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 90% recycled polypropylene mixture PP B336-GY31, 6% polypropylene K7227H, 1% toughening agent POE 8842, 1% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 0.5% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0030] Example 5 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 21.45% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.1% long-term antioxidant PS800, 0.1% modified epoxy resin, 0.5% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0031] Example 6 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 20.77% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.3% antioxidant Irganox 1076, 0.08% antioxidant Irganox 1098, 0.2% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 0.5% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0032] Example 7 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 19.6% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.4% antioxidant Irganox 1076, 0.1% antioxidant Irganox 1098, 0.2% antioxidant Irgafos 168, 0.2% long-term antioxidant PS800, 1.5% modified epoxy resin, 0.5% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0033] Example 8 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 19.5% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.4% weathering agent LA-402AF, 0.4% antioxidant Irganox 1076, 0.1% antioxidant Irganox 1098, 0.2% antioxidant Irgafos 168, 0.2% long-term antioxidant PS800, 1.5% modified epoxy resin, 0.5% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0034] Example 9 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 21.5% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 0.1% metal passivator MD1024, and 0.1% metal carbonate hydrate.

[0035] Example 10 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 21.1% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 0.4% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0036] Embodiment 11 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 20.7% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 0.8% metal passivator MD1024, and 0.2% metal carbonate hydrate.

[0037] Example 12 This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that the automotive good appearance anti-aging recycled polypropylene composite material of this embodiment is prepared from the following components in weight percentage: 30% recycled polypropylene mixture PP B336-GY31, 20.45% polypropylene K7227H, 25% toughening agent POE 8842, 22% talcum powder KCM-6300, 0.3% weathering agent LA-402AF, 0.2% antioxidant Irganox 1076, 0.05% antioxidant Irganox 1098, 0.1% antioxidant Irgafos 168, 0.15% long-term antioxidant PS800, 0.5% modified epoxy resin, 1% metal passivator MD1024, and 0.25% metal carbonate hydrate.

[0038] Comparative Example 1 This comparative example adopts the same implementation method as Example 2, but differs from Example 2 in that: The preparation method of the recycled polypropylene composite material of this comparative example comprises the following steps: S1. Weigh the recycled polypropylene mixture, polypropylene, toughening agent, filler, weathering agent, antioxidant, long-acting antioxidant, modified epoxy resin, metal passivator and metal carbonate hydrate in proportion, and add 50 to 100% of the total weight of the filler, the recycled polypropylene mixture, polypropylene, toughening agent, weathering agent, antioxidant, long-acting antioxidant, epoxy resin, metal passivator and metal carbonate hydrate to a high mixer and mix at a speed of 450 to 600 rpm for 50 to 80 seconds to obtain a premix; S2. The premix is ​​added through the main feeding port of the twin-screw extruder, and the remaining filler in step S1 is added from the side feeding port, and the premix is ​​plasticized and melted into a mixed melt through the extruder, wherein the speed of the twin-screw extruder is 450-600 rpm, the temperature zone 1 is 100° C., the other temperatures are 170° C.-200° C., and the vacuum degree is above -0.06 MPa; the mixed melt is extruded into material strips through a die, and after water cooling, it enters a pelletizer and is cut into plastic particles; the plastic particles are screened out with qualified particles with a diameter of 2-3.5 mm through a vibrating screen, and after falling into the discharge port of the vibrating screen, they are sucked into a homogenizing tank to obtain a recycled polypropylene composite material.

[0039] Comparative Example 2 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that the preparation method of the recycled polypropylene composite material in this comparative example includes the following steps: S1. Weigh the recycled polypropylene mixture, polypropylene, toughening agent, filler, weathering agent, antioxidant, long-acting antioxidant, modified epoxy resin, metal passivator and metal carbonate hydrate in proportion, and add 50 to 100% of the total weight of the filler, the recycled polypropylene mixture, polypropylene, toughening agent, weathering agent, antioxidant, long-acting antioxidant, epoxy resin, metal passivator and metal carbonate hydrate to a high mixer and mix at a speed of 450 to 600 rpm for 50 to 80 seconds to obtain a premix; S2. Add three layers of filter screen between the extruder barrel flange and the die flange. The mesh size of the two outer layers is 20-40 mesh, and the mesh size of the middle layer is 80-120 mesh. The replacement frequency of the three layers of filter screen is 2-4 hours / time; S3. Place a magnet rack at the discharge port of the vibrating screen. The magnetic field strength of the magnet rack is 10000~15000Gs. The cleaning frequency of the magnet rack is 2~4h / time; S4. The premix is ​​added through the main feeding port of the twin-screw extruder, and the remaining filler in step S1 is added from the side feeding port, and the premix is ​​plasticized and melted into a mixed melt through the extruder, wherein the rotation speed of the twin-screw extruder is 450-600 rpm, the temperature zone 1 is 100° C., the other temperatures are 170° C.-200° C., and the vacuum degree is above -0.06 MPa; the mixed melt is extruded into material strips through a die, and after water cooling, it enters a pelletizer and is cut into plastic particles; the plastic particles are screened out with qualified particles with a diameter of 2-3.5 mm through a vibrating screen, and after falling into the discharge port of the vibrating screen, they are sucked into a homogenizing tank to obtain a recycled polypropylene composite material.

[0040] Comparative Example 3 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that the preparation method of the recycled polypropylene composite material in this comparative example includes the following steps: S1. Weigh the recycled polypropylene mixture, polypropylene, toughening agent, filler, weathering agent, antioxidant, long-acting antioxidant, modified epoxy resin, metal passivator and metal carbonate hydrate in proportion, and add 50 to 100% of the total weight of the filler, the recycled polypropylene mixture, polypropylene, toughening agent, weathering agent, antioxidant, long-acting antioxidant, epoxy resin, metal passivator and metal carbonate hydrate to a high mixer and mix at a speed of 450 to 600 rpm for 50 to 80 seconds to obtain a premix; S2. Place a magnet rack above the main feed port of the extruder (i.e. the position where all premixes need to pass). The magnetic field strength of the magnet rack is 10000~15000Gs, and the cleaning frequency of the magnet rack is 2~4h / time; S3. Place a magnet rack at the discharge port of the vibrating screen. The magnetic field strength of the magnet rack is 10000~15000Gs. The cleaning frequency of the magnet rack is 2~4h / time; S4. The premix is ​​added through the main feeding port of the twin-screw extruder, and the remaining filler in step S1 is added from the side feeding port, and the premix is ​​plasticized and melted into a mixed melt through the extruder, wherein the rotation speed of the twin-screw extruder is 450-600 rpm, the temperature zone 1 is 100° C., the other temperatures are 170° C.-200° C., and the vacuum degree is above -0.06 MPa; the mixed melt is extruded into material strips through a die, and after water cooling, it enters a pelletizer and is cut into plastic particles; the plastic particles are screened out with qualified particles with a diameter of 2-3.5 mm through a vibrating screen, and after falling into the discharge port of the vibrating screen, they are sucked into a homogenizing tank to obtain a recycled polypropylene composite material.

[0041] Comparative Example 4 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that the preparation method of the recycled polypropylene composite material in this comparative example includes the following steps: S1. Weigh the recycled polypropylene mixture, polypropylene, toughening agent, filler, weathering agent, antioxidant, long-acting antioxidant, modified epoxy resin, metal passivator and metal carbonate hydrate in proportion, and add 50 to 100% of the total weight of the filler, the recycled polypropylene mixture, polypropylene, toughening agent, weathering agent, antioxidant, long-acting antioxidant, epoxy resin, metal passivator and metal carbonate hydrate to a high mixer and mix at a speed of 450 to 600 rpm for 50 to 80 seconds to obtain a premix; S2. Place a magnet rack above the main feed port of the extruder (i.e. the position where all premixes need to pass). The magnetic field strength of the magnet rack is 10000~15000Gs, and the cleaning frequency of the magnet rack is 2~4h / time; S3. Add three layers of filter screen between the extruder barrel flange and the die flange. The mesh size of the two outer layers is 20-40 mesh, and the mesh size of the middle layer is 80-120 mesh. The replacement frequency of the three layers of filter screen is 2-4 hours / time; S4. The premix is ​​added through the main feeding port of the twin-screw extruder, and the remaining filler in step S1 is added from the side feeding port, and the premix is ​​plasticized and melted into a mixed melt through the extruder, wherein the rotation speed of the twin-screw extruder is 450-600 rpm, the temperature zone 1 is 100° C., the other temperatures are 170° C.-200° C., and the vacuum degree is above -0.06 MPa; the mixed melt is extruded into material strips through a die, and after water cooling, it enters a pelletizer and is cut into plastic particles; the plastic particles are screened out with qualified particles with a diameter of 2-3.5 mm through a vibrating screen, and after falling into the discharge port of the vibrating screen, they are sucked into a homogenizing tank to obtain a recycled polypropylene composite material.

[0042] Comparative Example 5 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that step S5 of the preparation method of the recycled polypropylene composite material in this comparative example is: S5. The premix is ​​added through the main feeding port of the twin-screw extruder, and the remaining filler in step S1 is added from the side feeding port. The premix is ​​plasticized and melted into a mixed melt through the extruder, wherein the rotation speed of the twin-screw extruder is 450-600 rpm, the temperature zone 1 is 140°C, the other temperatures are 220°C-240°C, and the vacuum degree is above -0.06MPa; the mixed melt is extruded into material strips through a die, and after water cooling, it enters a pelletizer and is cut into plastic particles; the plastic particles are screened out with qualified particles of 2-3.5mm in diameter through a vibrating screen, and after falling into the discharge port of the vibrating screen, they are sucked into a homogenizing tank to obtain a good appearance anti-aging recycled polypropylene composite material for automobiles.

[0043] Comparative Example 6 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that: in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.2%, the weight percentage of weathering agent LA-402AF is 0.1%, and the weight percentages of the remaining components are the same as those in Example 2.

[0044] Comparative Example 7 This comparative example adopts the same implementation as Example 9, and the difference from Example 9 is that in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.52%, the weight percentage of antioxidant Irganox1098 is 0.03%, and the weight percentages of the remaining components are the same as those in Example 2.

[0045] Comparative Example 8 This comparative example adopts the same implementation as Example 9, and the difference from Example 9 is that in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.48%, the weight percentage of antioxidant Irganox1098 is 0.07%, and the weight percentages of the remaining components are the same as those in Example 2.

[0046] Comparative Example 9 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that: in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.3%, the weight percentage of antioxidant Irganox 1076 is 0.05%, and antioxidant Irganox 1098 and antioxidant Irgafos 168 are not added. The weight percentages of the remaining components are the same as those in Example 2.

[0047] Comparative Example 10 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that: in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.3%, and the antioxidant Irganox 1076 and the antioxidant Irgafos 168 are not added, and the weight percentages of the remaining components are the same as those in Example 2.

[0048] Comparative Example 11 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that: in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.3%, the weight percentage of antioxidant Irgafos 168 is 0.05%, and antioxidant Irganox 1076 and antioxidant Irgafos 1098 are not added, and the weight percentages of the remaining components are the same as those in Example 2.

[0049] Comparative Example 12 This comparative example adopts the same implementation method as Example 2, and the difference from Example 2 is that: in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.15%, no long-acting antioxidant PS800 is added, and the weight percentages of the remaining components are the same as those in Example 2.

[0050] Comparative Example 13 This comparative example adopts the same implementation method as Example 2, and the difference from Example 2 is that in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 20.9%, the weight percentage of long-acting antioxidant PS800 is 0.25%, and the weight percentages of the remaining components are the same as those in Example 2.

[0051] Comparative Example 14 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that: in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.5%, no modified epoxy resin is added, and the weight percentages of the remaining components are the same as those in Example 2.

[0052] Comparative Example 15 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that: in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.5%, no metal passivator MD1024 is added, and the weight percentages of the remaining components are the same as those in Example 2.

[0053] Comparative Example 16 This comparative example adopts the same implementation as Example 2, and the difference from Example 2 is that: in the recycled polypropylene composite material of this comparative example: the weight percentage of polypropylene K7227H is 21.2%, no metal carbonate hydrate is added, and the weight percentages of the remaining components are the same as those in Example 2.

[0054] Test Case The composite materials obtained in the above Examples 1-12 and Comparative Examples 1-16 were subjected to the following performance tests: (1) Thermal aging performance test (powdering time): The recycled polypropylene composite materials prepared in the above Examples 1-12 and Comparative Examples 1-16 were injection molded into a square plate of 80 mm*50 mm*2.5 mm and placed in a constant temperature oven at 150°C. The time when the powdering area on the surface of the square plate reached 5% was recorded; (2) Light aging performance test (color difference ∆E): The recycled polypropylene composite materials prepared in the above Examples 1-12 and Comparative Examples 1-16 were injection molded into a square plate of 80 mm*50 mm*2.5 mm. After 5 cycles of testing according to the Volkswagen interior light aging standard PV1303, the changes in L, a, and b values ​​before and after light aging, i.e., ∆E, were tested. (3) Light aging performance test (appearance: powdering): The recycled polypropylene composite materials prepared in the above Examples 1-12 and Comparative Examples 1-16 were injection molded into a square plate of 80 mm*50 mm*2.5 mm. The powdering of the square plate was tested for 5 cycles according to the Volkswagen car interior light aging standard PV1303. If the square plate was powdered, it was completely powdered when the powdering area was 100%, and the rest was partial powdering. (4) Light aging performance test (appearance: sticky): The recycled polypropylene composite materials prepared in the above Examples 1-12 and Comparative Examples 1-16 were injection molded into a square plate of 80 mm*50 mm*2.5 mm. After 5 cycles of testing according to Volkswagen standard PV1306, the square plate was lightly touched with a finger to evaluate whether the square plate was sticky. (5) Pockmarks: The recycled polypropylene composite materials prepared in the above Examples 1-12 and Comparative Examples 1-16 were injection molded into a square plate of 100 mm*100 mm*2.5 mm. The number of pinhole-like pits with a diameter of ≥0.2 mm on the square plate was visually observed. If the number of pinhole-like pits with a diameter of ≥0.2 mm exceeded 5, it was evaluated as having pits; (6) Bulging: The recycled polypropylene composite materials prepared in the above Examples 1-12 and Comparative Examples 1-16 were injection molded into a square plate of 100 mm*100 mm*2.5 mm. The square plate was visually inspected to see if there were protrusions with a diameter of ≥1 mm. If so, it was evaluated as having bulging.

[0055] The above performance test results are shown in Table 1, Table 2, Table 3, Table 4, and Table 5.

[0056] Table 1 Amounts of components and test results of Examples 1-6

[0057] Table 2 Amounts of components and test results of Examples 7-12

[0058] Table 3 Dosages of components and test results of comparative examples 1-6

[0059] Table 4 Comparative Examples 7-12 Dosages of each component and test results

[0060] Table 5 Dosages of components and test results of comparative examples 13-16

[0061] From the results in Tables 1 to 5, we can see that: From the test results of Examples 1-4 in Table 1, it can be seen that for the recycled polypropylene composite material produced according to the method of the present application, as the proportion of the recycled polypropylene mixture increases, the heat aging time decreases from 1388h to 1034h, and the color difference after light aging increases from 0.53 to 1.23, that is, the heat aging and light aging properties are both decreasing, and even if the addition ratio of the recycled polypropylene mixture reaches 90%, the appearance is still free of pitting and bulging, the powdering time after heat aging is still more than 1000h, the color difference after light aging ∆E≤3, and the appearance is qualified, that is, the appearance, heat aging and light aging properties can still meet the requirements for automobile use; From the test results of Examples 5-7 in Tables 1 and 2, it can be seen that with the increase in the addition ratio of the antioxidant, the long-acting antioxidant and the modified epoxy resin, the heat aging time increases from 1186h to 1324h, indicating that the antioxidant and the synergistic long-acting antioxidant and the modified epoxy resin can effectively improve the heat aging properties of the composite material; From the test results of Example 2 and Examples 9-12 in Table 1 and Table 2, it can be seen that as the addition ratio of the metal passivator and the metal carbonate hydrate increases, the heat aging time increases from 1085h to 1396h, and the color difference after light aging decreases from 1.18 to 0.76, indicating that as the ratio of the metal passivator and the metal carbonate hydrate increases, the complexation effect on the metal and the protective effect of the additive are also enhanced, so the heat aging and light aging properties are also improved; It can be seen from the test results of Examples 1-12 in Table 1 and Table 2 that the appearance pitting and bulging of the composite materials of Examples 1-12 can meet the requirements for automobile use, that is, according to the preparation method of the present invention, the infusible resin, metal and impurities in the recycled polypropylene mixture can be significantly filtered, so that the molded product has a good appearance without pitting, bulging and other defects; It can be seen from the comparison between Example 2 and Comparative Example 1 that the steps S2-S4 of the preparation method of the present application were not used in the preparation process of Comparative Example 1, resulting in a large amount of infusible resin, metal and impurities in the composite material, so that pitting, bulging and other defects appeared in the appearance. At the same time, due to the presence of a large amount of metal ions in the composite material, the aging of the catalytic composite material was accelerated under the action of heat and light, and the thermal aging and light aging properties of the composite material were reduced. Therefore, the thermal aging time was only 183h, and the color difference after light aging was large, reaching 4.32, and the sample was completely powdered; It can be seen from Example 2 that compared with Comparative Examples 2-4, Comparative Examples 2, 3, and 4 did not use the S2, S3, and S4 steps of the preparation method of the present invention during the preparation process, resulting in a certain amount of infusible resin, metal, or impurities in the composite material, so the appearance still has pitting, bulging, and other defects. At the same time, due to the presence of a certain amount of metal ions in the composite material, the aging of the catalytic composite material is accelerated under the action of heat and light, which reduces the thermal aging and light aging properties of the material to a certain extent. Therefore, the thermal aging time is reduced from 1209h in Example 2 to 785-883h, and the color difference after light aging is also increased from 0.91 in Example 2 to 2.93-3.83, and the sample is partially powdered; It can be seen from Example 2 compared with Comparative Example 5 that when the extruder temperature exceeds 220°C, the resin in the recycled polypropylene mixture forms a molten state and can pass through the filter, resulting in that the resin in the recycled polypropylene mixture cannot be completely removed, so pitting and bulging appear on the appearance, and the thermal aging and light aging properties of the composite material are affected; It can be seen from the comparison between Example 2 and Comparative Example 6 that when the weathering agent is added at an amount lower than 0.2% of the present invention, degradation is serious after light aging, the color difference reaches 5.32, the sample is completely powdered, and the light aging performance cannot meet the requirements for automobile use; It can be seen from Example 9 that when the amount of antioxidant 1098 added is less than 20% of that of 1076, the heat aging time is reduced from 1085 to 782, indicating that during the heat aging process, antioxidant 1076 cannot play an antioxidant role on part of the resin in the recycled polypropylene mixture, resulting in reduced heat aging performance of the composite material; when the amount of antioxidant 1098 added is higher than 30% of antioxidant 1076, the heat aging performance does not change much, indicating that when antioxidant 1098 exceeds the amount required for part of the resin in the recycled polypropylene mixture, it can no longer effectively increase the heat aging performance of the composite material, and therefore has a low cost performance; It can be seen from Example 2 that when the amount of the main and auxiliary antioxidants added is less than 0.1% of the amount added in the present invention, the heat aging time is reduced from 1209h to 269-289h, indicating that the amount of the main and auxiliary antioxidants is too small to effectively achieve the purpose of anti-oxidation; It can be seen from Example 2 compared with Comparative Examples 12-13 that when the addition amount of the long-acting antioxidant is less than 0.1%, the heat aging time is reduced from 1209h to 465h, which cannot meet the requirements for automobile use; when the addition amount of the long-acting antioxidant is higher than 0.2%, although the heat aging time is increased to 1265h, stickiness occurs during light aging, which cannot meet the requirements for automobile use; It can be seen from Example 2 that when the amount of modified epoxy resin added is lower than 0.1% of the amount added in the present invention, the heat aging time is reduced from 1209h to 582h, indicating that insufficient modified epoxy resin cannot completely consume free radicals and cannot play a synergistic antioxidant role, so the heat aging performance is reduced; It can be seen from Example 2 that when the amount of metal passivator added is lower than 0.1% of the amount of the present invention, the heat aging time is reduced from 1209h to 358h, the color difference after light aging reaches 3.92, and the sample is completely powdered, indicating that when the amount of metal passivator added is insufficient, it cannot form a complex with high thermal stability with all metals, and there are still active metal ions in the composite material that catalyze the degradation of the composite material, resulting in reduced heat aging and light aging performance; It can be seen from Example 2 that when the amount of metal carbonate hydrate added is lower than 0.1% of the amount added in the present invention, the heat aging time is reduced from 1209 h to 637 h, the color difference after light aging reaches 4.09, and the sample is completely powdered. That is, when the amount of metal carbonate hydrate added is insufficient, the acidic substances and anions in the composite material cannot be effectively neutralized, resulting in insufficient activity of each additive and failure to provide stable heat aging and light aging properties.

[0062] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0063] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A good appearance anti-aging recycled polypropylene composite material for automobiles, characterized in that: The invention is prepared from the following components in weight percentage: 10% to 90% of recycled polypropylene mixture, 5% to 70% of polypropylene, 1% to 25% of toughening agent, 1% to 22% of filler, 0.2% to 0.5% of weathering agent, 0.1% to 0.8% of antioxidant, 0.1% to 0.2% of long-acting antioxidant, 0.1% to 1.5% of modified epoxy resin, 0.1% to 1.0% of metal passivator and 0.1% to 0.25% of metal carbonate hydrate.

2. The automotive good appearance anti-aging recycled polypropylene composite material according to claim 1, characterized in that: The invention is prepared from the following components in weight percentage: 30% to 50% of recycled polypropylene mixture, 20% to 40% of polypropylene, 8% to 15% of toughening agent, 10% to 22% of filler, 0.2% to 0.4% of weathering agent, 0.3% to 0.6% of antioxidant, 0.1% to 0.19% of long-acting antioxidant, 0.5% to 1.0% of modified epoxy resin, 0.4% to 0.8% of metal passivator and 0.1% to 0.2% of metal carbonate hydrate.

3. The automotive good appearance anti-aging recycled polypropylene composite material according to claim 1, characterized in that: The recycled polypropylene mixture is composed of one or more of resin, filler, metal and impurities, the resin is at least one of PP, PE, ABS, PC, PBT, PET, PA6 and PA66, the filler is at least one of talcum powder, calcium carbonate, mica, wollastonite, magnesium sulfate whisker and barium sulfate; the ash content of the recycled polypropylene mixture is ≤5%, and the density is ≤0.93g / cm 3 , polypropylene content ≥90%.

4. The automotive good appearance anti-aging recycled polypropylene composite material according to claim 1, characterized in that: The recycled polypropylene mixture is post-consumer recycled polypropylene material and / or post-industrial recycled polypropylene material.

5. The automotive good appearance anti-aging recycled polypropylene composite material according to claim 1, characterized in that: The polypropylene is homopolymer polypropylene and / or copolymer polypropylene; And / or, the toughening agent is at least one of ethylene-octene copolymer, polyethylene, hydrogenated styrene-butadiene-styrene block copolymer and ethylene propylene diene monomer rubber; And / or, the filler is at least one of talc, calcium carbonate, mica, wollastonite, magnesium sulfate whisker, and barium sulfate; And / or, the weathering agent is hindered amine light stabilizer LA-402AF or hindered amine light stabilizer UV-3808PP5.

6. The automotive good appearance anti-aging recycled polypropylene composite material according to claim 1, characterized in that: The antioxidant comprises a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is a composite of a hindered phenol antioxidant 1076 and a hindered phenol antioxidant 1098 in a mass ratio of 1:(0.2-0.3), and the secondary antioxidant is a phosphite antioxidant 168; And / or, the long-acting antioxidant is at least one of didodecanol thiodipropionate and distearyl thiodipropionate.

7. The automotive good appearance anti-aging recycled polypropylene composite material according to claim 1, characterized in that: The modified epoxy resin is prepared from an epoxy resin modified by an alicyclic epoxy polysiloxane, wherein the number average molecular weight of the alicyclic epoxy polysiloxane is 800-1200 g / mol, and the epoxy value is 0.5-0.

8.

8. The automotive good appearance anti-aging recycled polypropylene composite material according to claim 1, characterized in that: The metal passivator is at least one of hydrazide compounds N,N'-bis[β(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, (3,5-di-tert-butyl-4-hydroxyphenyl)propionate oxalyl(diimino-2,1-ethylene ester), and N-salicylicylaminophthalimide; And / or, the metal carbonate hydrate has a MgO content of 34.1% to 35.8%, an Al2O3 content of 18.5% to 21.5%, and a molar ratio of MgO to Al2O3 of 0.042 to 0.05:

1.

9. A method for preparing a good-appearance anti-aging recycled polypropylene composite material for vehicles as claimed in any one of claims 1 to 8, characterized in that: It includes the following steps: S1. Weigh the recycled polypropylene mixture, polypropylene, toughening agent, filler, weathering agent, antioxidant, long-acting antioxidant, modified epoxy resin, metal passivator and metal carbonate hydrate in proportion, and mix the filler, recycled polypropylene mixture, polypropylene, toughening agent, weathering agent, antioxidant, long-acting antioxidant, epoxy resin, metal passivator and metal carbonate hydrate accounting for 50 to 100% of the total weight of the filler to obtain a premix; S2. Place a magnet rack above the main feed port of the extruder; S3. A filter mechanism is provided at the connection between the barrel and the die of the extruder; S4. Place a magnet rack at the discharge port of the vibrating screen; S5. The premix is ​​added from the main feed port of the extruder, and the remaining filler is added from the side feed port of the extruder, melted, extruded, granulated, and screened with a vibrating screen to obtain a good appearance anti-aging recycled polypropylene composite material for automobiles.

10. The method for preparing the automotive good appearance anti-aging recycled polypropylene composite material according to claim 9, characterized in that: In step S1, the mixing is carried out in a high speed mixer at a speed of 450 to 600 rpm for 50 to 80 seconds; And / or, in steps S2 and S4, the magnetic field strength of the magnet frame is 10000-15000 Gs, and the cleaning frequency of the magnet frame is 2-4 hours / time; And / or, in step S3, the filter mechanism includes three layers of filters, the mesh number of the middle layer filter is 80-120 meshes, the mesh number of the outer two layers of filters is 20-40 meshes, and the replacement frequency of the three layers of filters is 2-4h / time; And / or, in step S5, the rotation speed of the extruder is 450-600 rpm, the temperature of the first zone of the extruder is 100° C., the temperature of the remaining zones of the extruder is 170° C.-200° C., and the vacuum degree of the extruder is above -0.06 MPa; and the screening is to screen out particles with a particle size of 2-3.5 mm.